Triglyceride-glucose body mass index and the risk of gestational diabetes mellitus: a population-based cohort study - Hu, Yezi; Xu, Li; Wang, Xiaojuan; Zhou, Zheng; Yang, Weiwei; Yuan, Yucui; Li, Jiaxing; Qiu, Shanhu; Wang, Yang; Wang, Xuyi; Xia, Pengbin; Wang, Shaohua; et al. (Frontiers in Nutrition, 2025)
BackgroundThe purpose of this analysis was to investigate the association between triglyceride-glucose body mass index (TyG-BMI) and gestational diabetes mellitus (GDM) in Chinese pregnant women.MethodsThis observational study utilized a cohort of pregnant women who were screened for GDM using the oral glucose tolerance test (OGTT). The TyG-BMI was calculated using the formula: TyG index = ln (fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2). TyG-BMI = TyG × BMI. Statistical analyses were performed to assess the correlation between TyG-BMI and gestational diabetes mellitus incidence.ResultsA total of 2,111 pregnant women were enrolled, out of which 281 (13.3%) women were diagnosed with gestational diabetes mellitus. Some differences existed between the TyG-BMI level groups with respect to various covariates (TG, BMI, age, TC, T-Bil, D-Bil, postpartum blood loss, vaginal birth, and GDM, p < 0.05). Compared to the lowest quartile of TyG-BMI, the third quartile of TyG-BMI is associated with the highest risk of developing gestational diabetes mellitus (OR: 1.8; 95%CI: 1.28 ~ 2.52). All models showed similar results. The stratified analyses were performed to examine whether the association between TyG-BMI and GDM was stable among different subgroups. None of the variables, including age (< 35 years and ≥35 years), premature delivery (yes or no), and vaginal birth (yes or no), significantly affected the association between TyG-BMI and GDM (all P for interaction > 0.05).ConclusionA cohort study of Chinese pregnant women concluded that TyG-BMI might be a valuable index for identifying IR in patients at high risk of gestational diabetes mellitus. TyG-BMI could be recommended as part of routine surveillance during early pregnancy.